Determination of Anticancer Activities of Organophosphazene Compounds Bearing Ether Groups on Human Cancer Cell Lines - Beytur, Asiye; Demir, Ilker; Koran, Kenan; Tekin, Suat; Gorgulu, Ahmet Orhan; Sandal, Suleyman (Wiley, 2017)
[Abstract Not Available]